RELATIONSHIP BETWEEN PARENTAL SMOKING BEHAVIOR AND ACUTE RESPIRATORY INFECTION INCIDENCE IN TODDLERS - Turangan , Eunike Eviani; Febriyanti , Irene Mutiara; Kristina , Natalia Karunia; Siregar , Deborah; Sinaga , Chriska (International Journal Multidisciplinary (IJMI), 2024)
Acute Respiratory Infection (ARI) is a leading cause of toddler illness. One contributing factor is parental smoking behavior, which exposes toddlers to secondhand smoke and increases their risk of URTI. Over the past five years, Banten Province reported 194,684 cases of ARI. This study aimed to analyze the relationship between parental smoking behavior and ARI incidence in Banten Province. A cross-sectional design was employed, with a sample of 399 parents of toddlers aged one to five years. Data collection took place from January to April 2022 using a convenience sampling technique and a questionnaire. Data analysis was performed using chi-square tests. The results indicated a significant association between parental smoking and ARI incidence in toddlers (p = 0.001). Toddlers with smoking parents were found to be 14.39 times more likely to develop ARI compared to those with non-smoking parents. The study recommends that parents, as primary caregivers, play a crucial role in preventing ARI by refraining from smoking around children, in cars, or within the home.